Prevalence of Leptospira Species in Environmental Soil and Water from National Parks in Sarawak, Malaysia - Chai, Fung Pui; Lesley, Maurice Bilung; Lela, Suut; Kasing, Apun (UNIMAS Publisher, 2015)
In Malaysia, there is an increasing number of reported leptospirosis cases which led to mortality. The infection is usually spread through the urine of infected animals and may contaminate the environmental soil and water. This study was conducted to determine the prevalence of Leptospira spp. in two national parks in Sarawak. A total of 50 soil and 60 water samples were collected from Tanjung Datu National Park (TDNP) and Bako National Park (BNP). The samples were filtered through sterile membrane filter prior to inoculation into modified semisolid Ellinghausen-McCullough-Johnson-Harris (EMJH) media added with 5-fluorouracil. The cultures were incubated at room temperature (28-30 °C) for 30 days before specific polymerase chain reaction (PCR) was conducted. PCR-positive samples were subjected to DNA sequencing. Out of the 110 environmental samples from two national parks in Sarawak, the prevalence of pathogenic, intermediate and saprophytic Leptospira was 0.9%, 5.5% and 0%, respectively. Results indicated that Leptospira borgpetersenii serovar Mini and Leptospira wolffii serovar Khorat were the pathogenic and intermediate Leptospira circulating in these study areas, respectively. Due to the ability of Leptospira to survive for months in environment, there is a risk of exposure to the public and tourists who visit these national parks. Increased awareness, continuous monitoring and effective preventive measures should be taken by local authorities to control leptospirosis outbreak.